Effects of organic solvent and temperature on the extraction of lutein from Scenedesmus sp biomass - Low, Keat Long; Ahmed, Iqbal; Ani Idris (Penerbit Universiti Kebangsaan Malaysia, 2019)
Lutein is a valuable bioactive compound that has various industrial applications. In nature, lutein is a yellow coloured isoprenoid polyene pigment, being produced by many photosynthetic organisms. With regard to Scenedesmus sp as the studied organism, this study aims to investigate the efficiency of microalgae-derived lutein extraction process. Repetitive solvent extraction method had been examined with four different organic solvents under different treatment temperatures for their lutein extraction effectiveness. Results showed that diethyl ether was the most effective organic solvent to extract lutein as compared to acetone, ethanol and dichloromethane. Under the extraction temperature of 60oC, diethyl ether was able to extract a total of 14.61 ± 0.31 mg/g of lutein from microalgae biomass. All the studied extraction treatments showed that lutein content in the extractants decreased as the number of extraction repetitions increased. By increasing the extraction repetition to 7 cycles using diethyl ether, treatment temperature at 60 °C resulted in a total of 16.07 ± 0.26 mg/g of lutein being extracted. Therefore, by selecting the most suitable organic solvent in lutein extraction, higher extraction treatment temperature shall provide sufficient energy required for the extraction process, thus further enhancing the overall extraction performance.